Des problèmes de change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Assion G.F. Lawson, du CAAK (Centre d'application agro-pastoral de Kovié), Lomé, Togo, nous fait part de sa frustration